fMRI brain activation changes following treatment of a first bipolar manic episode - Strakowski, Stephen M; Fleck, David E; Welge, Jeffrey; Eliassen, James C; Norris, Matthew; Durling, Michelle; Komoroski, Richard A; Chu, Wen-Jang; Weber, Wade; Dudley, Jonathan A; Blom, Thomas J; Stover, Amanda; et al. (Bipolar disorders, 2016)
Objectives We tested the hypothesis that, with treatment, functional magnetic resonance imaging (fMRI) regional brain activation in first‐episode mania would normalize – i.e., that differences from healthy subjects would diminish over time, and would be associated with clinical remission status, potentially identifying neuroanatomic treatment response markers. Methods Forty‐two participants with bipolar I disorder were recruited during their first manic episode, pseudo‐randomized to open‐label lithium or quetiapine, and followed for 8 weeks. fMRI scans were obtained at baseline and then after 1 and 8 weeks of treatment, while participants performed a continuous performance task with emotional distracters. Healthy participants received fMRI scans at these same intervals. Specific region‐of‐interest (ROI) activations within prefrontal emotional networks were assessed as potential measures of treatment response. Results ROI data were reduced using exploratory factor analysis, which identified five factors that were organizationally consistent with functional anatomic models of human emotion modulation. Half of the participants with bipolar disorder achieved remission by Week 8 and were contrasted with the other half that did not. Analyses demonstrated that, in the bipolar disorder group in general, treatment led to decreases in activation across brain regions toward healthy subject values. However, differences in activation changes were observed between subjects with bipolar disorder who did or did not achieve remission in subcortical and amygdala factors. Conclusions These findings provide evidence for potential neuroanatomic treatment response markers in first‐episode bipolar disorder.